Valuing American Put Options Using Gaussian Quadrature - Sullivan, Michael A. (Review of Financial Studies, 2000)
Journal Article Valuing American Put Options Using Gaussian Quadrature Get access Michael A. Sullivan Michael A. Sullivan Office of the Comptroller of the Currency Address correspondence to Michael A. Sullivan, Office of the Comptroller of the Currency, 250 E. St. SW, Washington, DC 20219, or e-mail:michael.sullivan@occ.treas.gov. Search for other works by this author on: Oxford Academic Google Scholar The Review of Financial Studies, Volume 13, Issue 1, January 2000, Pages 75–94, https://doi.org/10.1093/rfs/13.1.75 Published: 15 June 2015